2021
DOI: 10.1007/s13201-021-01400-w
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evaluation of the effects of mine discharges on surface water resources for irrigation: a case study of the Enyigba Mining District, Southeast Nigeria

Abstract: Mining activities generate much wastes which degenerate into various geochemical components and affect the natural composition of surface water resources. They cause Acid Mine Drainage (AMDs) and influence the hydrochemical evolution of the hydrogeological systems. This study employed hydrochemical parameters to characterize and evaluate the effects of mine discharges on irrigation surface water in the mining district of Enyigba, SE Nigeria. Twenty-four water samples were collected from surface water sources u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…For a better understanding of the exchange of ions Ca 2+ / (HCO 3 ¯ + SO 4 2 ¯) was plotted against Na + /Cl¯. Figures 7a and 7b showed that sampling points were categorized under natural state, results from Figure 7a and 7b revealed that natural salt dissolution such as carbonates rock, and silicate is the main processes controlling groundwater chemistry within the study area, this is in line with previous studies by [2] . [1] pointed out that TDS and TH are two major important parameters reflecting the quality of groundwater In this study.…”
Section: Gibbs Plotsupporting
confidence: 86%
See 4 more Smart Citations
“…For a better understanding of the exchange of ions Ca 2+ / (HCO 3 ¯ + SO 4 2 ¯) was plotted against Na + /Cl¯. Figures 7a and 7b showed that sampling points were categorized under natural state, results from Figure 7a and 7b revealed that natural salt dissolution such as carbonates rock, and silicate is the main processes controlling groundwater chemistry within the study area, this is in line with previous studies by [2] . [1] pointed out that TDS and TH are two major important parameters reflecting the quality of groundwater In this study.…”
Section: Gibbs Plotsupporting
confidence: 86%
“…Results obtained from the model revealed that groundwater collected from ARG and EAG fell within high Ca + Mg + SO 4 + Cl hydrogeochemical facies as shown in Figure 6a and 6b. The previous study within the study area revealed that groundwater was classified as moderately hard [2] , the presence of Ca and Mg ions, is the primary cause of hardness in groundwater within the study area. On general note water with high Ca+Mg is said to be hard.…”
Section: Gibbs Plotmentioning
confidence: 87%
See 3 more Smart Citations